Reasons for Lying in Kindergarten Children from the Kindergarten Teachers’ Point of View: A Comparative Study between Males and Females: سجلاء فائق هاشم , كلثوم عبد عون ردام (Journal of the College of Education for Women, 2021)
Lying is considered a dangerous tendency among children if it has become a habit. It results in many social problems, such as child’s loss of confidence, lack of others’ respect to him, and his lack of respect to the desired values ​​of the society, such as honesty and trust. Consequently, he will be led to a deviation when he becomes old; especially if the child’s socially unaccepted behavior has not been directed. The research, thus, aims to examine the causes of lying in the most important stage of children’s life; that is, between (4-6) years. Such an aim helps to know about the individual reasons of lying among males and females from teachers’ perspectives. To meet the objective of the study, a number of (128) children has been randomly selected from the children of the Kindergarten Department during the academic year 2019-2020, together with (28) she-teachers. In addition, a questionnaire has been designed for the purpose of discovering the reasons behind a child’s lying in the Kindergarten. The researchers have used many statistical means, such as: T-test for one sample and T-test for two independent samples, Pearson correlation coefficient, and Kay square to find the difference between home and kindergarten regarding reasons of lying. Results have shown that the fe(male) children in the kindergarten live in a social environment that lacks honesty; especially the case with male children. Moreover, female kindergarten children enjoy a wide imagination; which is characterized by being exaggerating, abundance,, creativity, and lack of adherence to concrete reality. The reasons to lie for kindergarten male children are higher than that of female’.